Morinda Citrifolia: Bioactivity and Utilization as Traditional Medicine and Food for the Community - Marina Silalahi (Research Collaboration Community (RCC), 2020)
Morindacitrifolia is a medicinal plant has been long used as traditional medicine and food ingredients. The plant bioactivity as a drug is related to its secondary metabolites. The writing of the article is based on a review to scientific published online or offline of the journals and books. In the Indonesian homegarden, the MC most found and cultivated as traditional medicinal. The fruit of MC has been commercialized as a health drink, but the anthraquinone content used as an indicator its security. The bioactivity of MC is antioxidant, anti-cancer, anti-microbial, anti-cancer, immunomodulatory, increasing central nervous system activity, anti-psychotic, antihepatitic and hepatoprotective. The 6-O- (b-D-glucopyranosyl) -1-O-octanoyl-b-D-glucopyranose and asperulosidic acid have anti-cancer activity, while pheophorbide a and pyropheophorbide a have anti-hepatitis activity.